PERFORMANCE OF TECHNOLOGY COMPONENT FOR CATTLE AS DETERMINANT FOR ACCELERATING INNOVATION ADOPTION TO SUPPORT “PSDS 2014” PROGRAMME IN EAST JAVA - Vyta W. Hanifah; R. Hendayana (Widyariset, 2011)
The study was assessing the performance of cattle component of technology as determinant for accelerating innovation adoption to support “PSDS 2014” programme in East Java. The assessments were conducted in three districts in East Java Province, which were Blitar, Kediri, and Lamongan. The fi fteen respondents were selected by purposive random sampling representing adopter of component technology. Data collected were characteristics of farmers and farming system, distance from source of information, and also supporting data from local govern-ment. The data were analyzed by qualitative descriptive, with Structure Conduct Performance approach. The results showed that technology performance has effects in accelerating adoption of technology components which are infl uenced by some factors, i.e. farming system characteristics, educational level and accessibility to source of technology information. Accessibility is the most important factor that defi nes how farmers receive information about new technology.